Politics and Financing of the National Education Budget - Ifna Nifriza; Yahya Yahya (Universitas Muhammadiyah Enrekang, 2023)
This research aims to describe the influence of politics on national education funding. The approach used in this study is a descriptive qualitative literature study, with categories of analysis based on the findings of previous researchers on education financing models. The results of this study indicate that education financing in Indonesia is currently a standard model that refers to government policies. Government intervention shows an increase in the education budget that exceeds the limit of securing an efficient allocation of resources and supporting economic growth. The education budget of 20% which is expected to be realized can cover education costs starting from elementary education, secondary education to higher education. The increase in the total allocation of the education budget is expected to have a positive impact on the renewal of the education system in the Republic of Indonesia. The increase in the budget is inseparable from the interference of politics and the authorities.